2011
DOI: 10.1021/ma2008817
|View full text |Cite
|
Sign up to set email alerts
|

A New Scenario of Shish-Kebab Formation from Homogeneous Solutions of Entangled Polymers: Visualization of Structure Evolution along the Fiber Spinning Line

Abstract: Self-assembly of ordered structures under the external fields is one of the most important and fundamental research themes in physical science of soft matters including polymers. The “shish-kebab” self-assembly is a most intriguing but fundamental crystalline superstructure formed in polymers under various flow fields. Nevertheless the mechanism of shish-kebab formation is not fully understood yet. In order to clarify the mechanisms for polymer solutions, we have investigated the flow-induced self-assembling s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 49 publications
(98 reference statements)
4
74
1
Order By: Relevance
“…At this point, it is sensible to conclude that the negative form birefringence component emerging after recovery originated from stacks of chain folded lamellar crystallites of PLA formed perpendicularly to the extended‐chain crystallites of PLA due to fibrillar‐to‐lamellar transformation, generating the so‐called shish–kebab structure. Such structure has been reportedly observed in several polymers subjected to flow field under solution or melt state as well as uniaxial hot‐stretching followed by annealing at very high temperature (in the melting temperature range) under stretched state . The unprecedented formation of shish–kebab structure at relatively low temperature under rubbery state discovered in this work presents the great technological significance, which would extend the borderline of the possibilities in designing material structure.…”
Section: Resultssupporting
confidence: 63%
“…At this point, it is sensible to conclude that the negative form birefringence component emerging after recovery originated from stacks of chain folded lamellar crystallites of PLA formed perpendicularly to the extended‐chain crystallites of PLA due to fibrillar‐to‐lamellar transformation, generating the so‐called shish–kebab structure. Such structure has been reportedly observed in several polymers subjected to flow field under solution or melt state as well as uniaxial hot‐stretching followed by annealing at very high temperature (in the melting temperature range) under stretched state . The unprecedented formation of shish–kebab structure at relatively low temperature under rubbery state discovered in this work presents the great technological significance, which would extend the borderline of the possibilities in designing material structure.…”
Section: Resultssupporting
confidence: 63%
“…7e) did not disappear even after the shear cessation at 124 C as shown in Fig. 7(f), the intensity of the streak-like SALS pattern further increased with t (Murase et al, 2005(Murase et al, , 2009(Murase et al, , 2011, and the solution after cooling showed the shishkebabs under TEM, as shown in Fig. 7(l).…”
Section: Figurementioning
confidence: 90%
“…Subsequent annealing and recrystallization of the off-line samples gave denser and shorter oriented shish-kebab structures at high stretching rates, compared with dense but longer structures at low stretching rates. Murase [25] gave a comprehensive study of the flow-induced self-assembling structures that evolve down a fibre spin-line for concentrated polymer solutions proposing a two-stage pathway for shish-kebab formation. Early stages saw the evolution of transient phases leading to string-like structures.…”
Section: Introductionmentioning
confidence: 99%